Efficacy and Safety of Brinzolamide as Add-On to Prostaglandin Analogues or β-Blocker for Glaucoma and Ocular Hypertension: A Systematic Review and Meta-Analysis - Liu, Yuanzhi; Zhao, Junyi; Zhong, Xiaoyan; Wei, Qiming; Huang, Yilan (Frontiers in Pharmacology, 2019)
Background: Brinzolamide as a carbonic anhydrase inhibitor could be Combined with other intraocular pressure (IOP) lowering drugs for glaucoma and ocular hypertension (OHT), but the efficacy was controversial. So, this study was to assessed the efficacy and safety of brinzolamide as add-on to prostaglandin analogues (PGAs) or β-blocker in treating patients with glaucoma or OHT who fail to adequately control IOP. Methods: We searched Pubmed, Embase, Medline, Cochrane Library and clinicaltrials.gov. from inception to October 4, 2018. Randomized controlled trials of brinzolamide as add on to PGAs or β-blocker for glaucoma and OHT were included. Meta-analysis was conducted by RevMan 5.3 software. Results: A total of 26 trials including 5583 patients were analyzed. Brinzolamide produced absolute reductions of IOP as a adjunctive therapy for patients with glaucoma or OHT. Brinzolamide and timolol were not significantly different in lowering IOP as add-on to PGAs (9 am: P=0.07; 12 am: P=0.66; 4 pm: P=0.66). Likewise, brinzolamide was as effective as dorzolamide in depressing IOP (9 am: P=0.59; 12 am: P=0.94; 4 pm: P=0.95). Compared with brimonidine (bid), a significant reduction from the baseline in IOP in brinzolamide (bid) at 9 am (P0.0001), however, the differences was cloudy in thrice daily subgroup (P=0.44); At 12 am, brinzolamide (bid) was similar to brimonidine (bid) in IOP-lowering effect (P=0.23), whereas brimonidine (tid) led to a greater IOP-lowering effect than brinzolamide (tid) (P=0.02). At 4 pm, brinzolamide (bid) was superior IOP-lowering effect compared with brimonidine (bid) (P=0.0003), conversely, the effect in brinzolamide (tid) was lower than brimonidine (tid) (P  0.0001). For the Safety, brinzolamide and dorzolamide had a higher incidences of taste abnormality, moreover, brinzolamide resulted in more blurred vision, dorzolamide resulted in more ocular discomfort and eye pain. Timolol resulted in more blurred vision and less conjunctival hyperemia. Brimonidine resulted in more ocular hyperemia. As to other adverse events (AEs) (conjunctivitis, eye pruritus, foreign body sensation in eyes and treatment-related AEs)，brinzolamide was similar to the other three active comparators. Conclusions: Brinzolamide, as add-on to PGAs or β-blocker, significantly decrease IOP of patients with refractory glaucoma or OHT and the AEs were tolerable.